Events Management Practices and Performance of Selected HEIs in National Capital Region: Inputs for Sustainable Business Generating Projects - Buenaventura, John Paul G.; Soriano, Elizabeth E (East Asian Journal of Multidisciplinary Research, 2024)
Events management practices played a crucial role in the success and performance of higher education institutions (HEIs) in implementing sustainable business generating projects. This study examined the inputs related to events management practices and their impact on the performance of selected HEIs in the context of sustainable business generating projects. The research aimed to provide insights into effective strategies and best practices that could enhance the success of these projects within HEIs. The study adopted a quantitative research approach, utilizing surveys to gather data from a sample of selected HEIs. The study identified key success factors and challenges faced by HEIs in managing events and sustaining their business generating initiatives. It also provided practical recommendations and guidelines for HEIs to optimize their events management practices and improve project performance. The research outcomes were valuable for HEI administrators, event managers, and other stakeholders involved in sustainable business generating projects within the higher education sector. By identifying effective strategies and practices, this study aimed to enhance the ability of HEIs to generate sustainable business opportunities through events and contribute to the overall development and reputation of these institutions. In conclusion, this study sought to bridge the gap in knowledge regarding events management practices and their impact on the performance of HEIs in sustainable business generating projects. The findings informed decision-making processes and enabled HEIs to implement effective and sustainable events management strategies, ultimately leading to enhanced project performance and long-term success.